Brotherhood of Kings - Podany, Amanda H.
1 online resource (423 pages)
Keywords: Over four thousand years ago ambassadors and merchants overcame all manner of obstacles in order to ally the kings of the ancient Near East together as self-proclaimed brothers. This book takes readers on a journey across time and space--from the 24th to the 14th century BCE, and through deserts and river valleys--to meet the colorful characters who first began to tie cultures together.